The Pengembangan Lembar Kerja Peserta Didik berbasis Model Problem Based Learning dengan Pendekatan Saintifik berbantuan Video untuk Meningkatkan Keterampilan Proses Sains - Elvi Suryanti; festiyed (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to produce a product in the form of Student Worksheets based on Problem based learning models with a video-assisted scientific approach to improve science process skills that are valid, practical, and effective. This study uses the Plomp model, namely preliminary research, prototyping phase, and assessment phase. The validity and practicality of the developed Student Worksheets were obtained through validation and practicality questionnaire instruments, the effectiveness of Student Worksheets on attitude competence used observation sheets, knowledge was carried out by giving tests to students, and science process skills using performance assessment sheets taken by observers learning takes place. The results of the Student Worksheet data analysis were declared valid with an average value of 0.86. The practicality assessment obtained an average value of 81.78 and 86.01 in the very practical category. The student worksheets were declared effective in the attitude competencies of students in the very good category and more than 85% of students obtained scores above the Minimum Completeness Criteria, in the knowledge competence experienced an increase in gain score of 0.63 in the medium category, and Assessment of science process skills obtained an average value of 85.51 with a very good predicate.